Motivational factors in adult, auditioned community choirs: The power of aesthetic experiences. (September 2019) - Redman, David J.; Bugos, Jennifer A.
The purpose of this study was to a) identify motivational factors to join and maintain membership in adult, auditioned community choirs; b) examine relationships between music achievement, music aptitude, and selected motivational factors; and c) examine the role of stress and anxiety as factors in choral participation. Participants ( N = 135) from four adult, auditioned community choirs participated in this study. Data was collected using measures of musical aptitude, vocal achievement, and a questionnaire relating to the topics of motivation, retention, and stress/anxiety informed by Cusp Catastrophe Theory. Results suggest that aesthetic motivation is a primary factor contributing to enrollment and retention in adult, auditioned community choirs. Experienced choral members perceive little stress or anxiety when learning or performing choral music; however, members believe that some stress may be beneficial to singing. Implications include the need for conductors to consider the importance of perceived aesthetic qualities when selecting choral literature. In addition, the impact of community ensembles on community cohesion, health benefits, and educational benefits may be related to motivational factors influencing continued participation.